A Review Of The Features Of Augmented Reality Science Textbook - Gopalan, Valarmathie; Zulkifli, Abdul Nasir; Faisal Mohamed, Nur Fadziana; Alwi, Asmidah; Che Mat, Ruzinoor; Abu Bakar, Juliana Aida; Saidin, Aeni Zuhana (2014)
This paper reviews several literatures concerning the features of Augmented Reality (AR) based textbook that could be applied for science learning in schools in order to make the learning process effective and interesting. The intervention of AR in science textbook could bring a tremendous impact on students’ attitude towards the science subject. Even though there are several other proven and astonishing technologies for learning, AR has been chosen because of its highly potential and immersive characteristics. AR overlays real and virtual environment and displays them simultaneously on a computer screen. This technology offers students with the ultimate imaginary and makes them feel the real experience with scientific concepts which is impossible to experience in real life. This paper identifies several interesting features that could be applied in science textbook. These features are able to cultivate positive attitude and motivate the students to perform well in the science subject. Even though, the existing textbook is comprehensive, there are some limitations that might influence students’ performance in the science subject. By adding some additional features into the textbook, it could overcome the limitations and motivates the students in the learning process. This paper will be of interest to researchers in the areas of Augmented Reality in education as well as science teachers in general. This paper aims to introduce AR based textbook so that it can be widely used in schools especially for science learning so as to motivate students to be more interested in science. The information about the features of Augmented Reality (AR) based textbook that have been discussed in this paper will hopefully be a very useful guidance for other researchers as well as science teachers in planning and developing their own AR based textbook